Lamotrigine-induced DRESS syndrome in a patient with mood disorder and NAGS deficiency: A case report - Şimşir, Serhat; Ray, Perihan Cam; Çelik, Gonca Gül; Tahiroğlu, Ayşegül Yolga; Kor, Deniz (Scientific Reports in Medicine, 2026)
N-acetyl glutamate synthase (NAGS) deficiency is a very rare autosomal recessive metabolic disease that affects the urea cycle and can cause serious morbidity and mortality. In these cases, mood disorders are rare, and potential side effects are important in the treatment of neurological and psychiatric conditions occurring due to the existing enzyme deficiency. In this study, a case of NAGS deficiency, epilepsy, and mood disorder, as well as drug rash with eosinophilia and systemic symptoms (DRESS) syndrome after lamotrigine use, is presented.